On the Temperature Dependence of the Rate Constant of the Bimolecular Reaction of Two Hydrated Electrons - S.L. Butarbutar; Y. Muroya; L.M. Kohan; S. Sanguanmith; J. Meesungnoen; J.-P. Jay-Gerin (Atom Indonesia, 2013)
It has been a longstanding issue in the radiation chemistry of water that, even though H2 is a molecular product, its “escape” yield g(H2) increases with increasing temperature. A main source of H2 is the bimolecular reaction of two hydrated electrons (e-aq). The temperature dependence of the rate constant of this reaction (k1), measured under alkaline conditions, reveals that the rate constant drops abruptly above ~150°C. Recently, it has been suggested that this temperature dependence should be regarded as being independent of pH and used in high-temperature modeling of near-neutral water radiolysis. However, when this drop in the e-aq self-reaction rate constant is included in low (isolated spurs) and high (cylindrical tracks) linear energy transfer (LET) modeling calculations, g(H2) shows a marked downward discontinuity at ~150°C which is not observed experimentally. The consequences of the presence of this discontinuity in g(H2) for both low and high LET radiation are briefly discussed in this communication. It is concluded that the applicability of the sudden drop in k1 observed at ~150°C in alkaline water to near-neutral water is questionable and that further measurements of the rate constant in pure water are highly desirable.Received:13 June 2013; Revised: 27 August 2013; Accepted: 28 August 2013